2015
DOI: 10.1016/j.bjorl.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vascular endothelial growth factor expression and presence of lymph node metastasis in advanced squamous cell carcinoma of the larynx

Abstract: Although vascular endothelial growth factor was expressed in a few cases, there was no correlation with the spread of cervical lymph metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Korampalli and Stafford 11 found no differences in terms of VEGF levels in early and advanced larynx tumors. Similar to our findings, no correlations were found between VEGF level and lymph node metastasis in several studies on larynx cancer 31,32 . However, Wang et al 33 reported a significant association between VEGF and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Korampalli and Stafford 11 found no differences in terms of VEGF levels in early and advanced larynx tumors. Similar to our findings, no correlations were found between VEGF level and lymph node metastasis in several studies on larynx cancer 31,32 . However, Wang et al 33 reported a significant association between VEGF and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our findings, no correlations were found between VEGF level and lymph node metastasis in several studies on larynx cancer. 31,32 However, Wang et al 33 reported a significant association between VEGF and lymph node metastasis. We think the role of VEGF in laryngeal carcinoma needs to be further investigated in order to better understand the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al even reported a strong association of VEGF expression with lymph node metastasis in primary laryngeal carcinomas [ 27 ]. In contrast, other studies did not reveal any association of angiogenesis with the presence of LN metastasis [ 25 , 28 ]. In our analysis there was no direct correlation between T- or N-stage and VEGF.…”
Section: Discussionmentioning
confidence: 67%
“…The prevalence of laryngeal carcinoma is increasing; it currently accounts for 1‒5% of all malignant tumors and 11‒22% of head and neck malignant tumors [ 2 , 3 ]. Further, tumor size, local invasion, spread into lymph nodes, and distant metastasis can affect the prognosis for laryngeal carcinoma [ 4 ]. Chemoradiotherapy is used to treat laryngeal carcinoma in its early stage, whereas surgery is widely used in its advanced stage, including total and partial laryngectomies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%